Thermal-mechanical dual stimuli responsive films for smart windows - Ku, Alene Ai Lin (Nanyang Technological University, 2020)
Demand for energy has been increasing with time, especially in building sectors. This is mainly due to heating and air-conditioning systems in buildings. Thus, there is a need to design smart windows, to regulate light and solar radiation entering and exiting buildings to reduce energy consumption. To alleviate this problem, many studies have been done on smart windows. However, they either have too complex mechanisms or are too expensive to commercialize. Hence, this research aims to devise a thermal mechanical dual-stimulus responsive film that is cost effective and works on a simple mechanism. The composite film consists of a bottom thin layer of SiO2 microparticles embedded in elastic PDMS, with a top thicker layer of PDMS embedded with VO2 nanoparticles. UV-vis spectrophotometry was conducted to quantify the change in transmittance. For smart window application, the Tlum is calculated to be 63.3% for both the 20oC/0%-elongated and the 95oC/0%-elongated, and 13.3% for the 20oC/80%-elongated sample. The ΔTsol is 7.2% for the thermochromic mode and 46.4% for the mechanochromic mode. It was concluded that VO2 and SiO2 particles were capable of optical modulations through its thermochromic and mechanochromic properties respectively.